Logic and the way of Jesus : thinking critically and Christianly - Dickinson, Travis (B & H Academic, 2022)
"In Logic and the Way of Jesus, philosophy professor Travis Dickinson recaptures the need for a Christian view of reality, highlighting the use of reason and evidence to develop and defend Christian beliefs. He demonstrates how Jesus employed logic in his teachings, surveys the basic concepts of logic, and marries those concepts with practical application. While Dickinson contends that Christians have failed to engage the culture deeply because they have failed to emphasize and value a Christian intellect, he offers encouragement that embracing the life of the Christian mind can impact the world for the cause and kingdom of Christ."--Publisher